Oral Glucose Tolerance Test for Universal screening for Gestational Diabetes Mellitus - Shrestha, Abha; Shakya, Rajani; Shrestha, Rabina; Karki, Sulata; Das, Seema; Shrestha, Priya; Rai, Anisha; Thapa, Saroj; Shrestha, Abha; Karmacharya, Biraj (Journal of Nepal Health Research Council, 2024)
Background: Gestational Diabetes Mellitus increased almost 30% in many countries, including underdeveloped countries and same in Nepal. Hospital-based studies in Nepal reported Gestational Diabetes Mellitus cases, with prevalence 2.48% in 2010 to 4.47% in 2019 emphasising on necessity of universal screening for Gestational Diabetes Mellitus.Methods: As part of implementation of Electronic Decision support System for Antenatal Care, in formative study clinical vignettes on Gestational Diabetes Mellitus case presented to six healthcare providers ( Incharges, Auxiliary Nurse, Midwives and Lab Assistants) from 3 primary healthcare facilities in Kavre and Dolakha districts, Nepal from October-December 2019. 19 Auxiliary Nurse, Midwives from 19 HCF of 4 districts (Kavre, Dolakha, Sindhuli, and Sindhupalchok, including where clinical vignette were applied trained to perform Oral Glucose Tolerance Test for 4 hours. In-depth Interviews conducted with 16 Auxiliary Nurse, Midwives (8 trained & 8 peer coached from selected 4 HCF to explore their perception & experiences of conducting Oral Glucose Tolerance Test and continuing it for future. Clinical vigenttes compared with PEN protocol and IDIs analyzed thematically. Results: Only 4/6 HCPs made probable diagnosis of Gestational Diabetes Mellitus. 217 Oral Glucose Tolerance Test performed, 24 found to have Gestational Diabetes Mellitus. In-depth Interviews showed Auxiliary Nurse, Midwives enthusiasts on implementing tests for Gestational Diabetes Mellitus and to continue what has been learnt in training. Some challenges; clients hesitate to stay 2 hours at facilities due to unavailability of transport and household work. Oral Glucose Tolerance Test trained Auxiliary Nurse, Midwives seem more confident in counselling and conducting Oral Glucose Tolerance Test than those peer coached. Conclusions: Administering Oral Glucose Tolerance Test seemed feasible in HCF settings despite some challenges. Training and continuing logistics supply from municipality level seems promising.Keywords: GDM: Nepal: OGTT: